Educação de profissionais de enfermagem Ingressantes em um hospital de ensino: contribuição da aprendizagem bimodal - Andrade, Cláudia Cristina Castro de (2016)
The hiring integration could always be a host process of the new cooperator, allowing him to receive orientation about the institution, providing a better performance of his professional activities and arousing on him a continuing search of new knowledge. Considering these premises, it was idealized and implemented by the segment of Continued Education of Hospital Santa Lucinda, of Pontifícia Universidade Católica de São Paulo, a program of capacitation to the recently hired ones, using real or simulated experiences in problematizations by using a blended learning as a way of learning to value the human potential of the involved professionals, motivating the significative learning by using active methodologies of learning. This study of qualitative approach with characteristics of participative research aimed at evaluating the blended method on the hiring learning of 14 technitians of nursing. The data collection was made by a self-administered survey form, which covered the characterization of the attendees, their perception on the capacitation program, besides sugestions and comments. The answers were organized according to the Collective Subject Speech and analyzed by means of the Thematic Analysis of the Content, Thematic Analysis modality. The testimonies were categorized in the fortresses, fragilities, content relevance and improvement suggestions. The participation on the integration program arouse feelings like: happiness, comfort, satisfaction, security, empowerment, motivation.The fragilities and suggestions given enabled a readequation and improvement of the program of admissional hiring, as much as also extending it to the other professionals of nursing of the institution